Get Rich or Fail Your Exam Tryin': Gender, Socioeconomic Status and Spillover Effects of Blended Learning - Adrian Mehic; Charlotta Olofsson (Lund University, School of Economics and Management, Department of Economics, 2021)
We evaluate a natural experiment at a Swedish university, in which students were randomized to either taking all their courses online, or to have some courses online and some on campus (blended learning). Our setting creates two groups for the online courses: One group with no access to campus whatsoever, and one group treated with campus classes in parallel, but unrelated, courses. We show that campus access in parallel courses improved academic performance in online courses only among female students with affluent parents. Detailed individual-level survey data suggests that there was no relationship between social status and adverse mental health amid the COVID-19 pandemic. Instead, by estimating each student's network position, linked with administrative data on parental income, we show that female students with wealthy parents have significantly less constrained social networks, enabling them to utilize scarcely available campus time to communicate with classmates more efficiently.
Keywords: I23; I28; J16; Z13; 330; COVID-19; blended learning; online education; social networks